2022
DOI: 10.1111/jon.12990
|View full text |Cite
|
Sign up to set email alerts
|

Brain oxygen extraction and neural tissue susceptibility are associated with cognitive impairment in older individuals

Abstract: Background and Purpose:We investigated the effects of aging, white matter hyperintensities (WMH), and cognitive impairment on brain iron levels and cerebral oxygen metabolism, known to be altered in Alzheimer's disease (AD), using quantitative susceptibility mapping and MR-based cerebral oxygen extraction fraction (OEF). Methods:In 100 individuals over the age of 50 (68/32 cognitively impaired/intact), OEF and neural tissue susceptibility (χ n ) were computed retrospectively from MRI multi-echo gradient echo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 91 publications
(170 reference statements)
1
13
0
Order By: Relevance
“…The OEF of cognitively impaired subjects was higher than that of those with cognitive integrity. The increase of WMH load in cognitive impairment subjects was significantly correlated with the decrease of OEF, but not in the cognitively intact ( 68 ).…”
Section: Application Of Multimodal Mri Techniques For Wmh and Cogniti...mentioning
confidence: 87%
See 2 more Smart Citations
“…The OEF of cognitively impaired subjects was higher than that of those with cognitive integrity. The increase of WMH load in cognitive impairment subjects was significantly correlated with the decrease of OEF, but not in the cognitively intact ( 68 ).…”
Section: Application Of Multimodal Mri Techniques For Wmh and Cogniti...mentioning
confidence: 87%
“…In addition, in concentric contours close to WMH, OEF gradually increased, and CBF decreased ( 66 ). WMH is related to OEF, but it will change due to the existence of cognitive impairment ( 68 ). The lower the OEF, the more severe the cognitive impairment, possibly due to reduced oxygen consumption resulting from reduced neural activity ( 67 ).…”
Section: Application Of Multimodal Mri Techniques For Wmh and Cogniti...mentioning
confidence: 99%
See 1 more Smart Citation
“…QQ-based OEF further showed higher OEF in the QSM hyperintense rim within choric active MS lesions than the rest of the lesions, which agrees with active inflammation in the rim. In dementia ( Chiang et al, 2022 ), QQ-based OEF showed positive associations with white matter hyperintensity, an important predictor of dementia. Also, QQ showed OEF abnormalities in brain tumor ( Shen et al, 2021 ) and preeclampsia ( Yang et al, 2022 ).…”
Section: Susceptibility-based Quantification Of Cerebral Oxygen Metab...mentioning
confidence: 98%
“…One study ( Chiang et al, 2022 ) combined QSM with qBOLD to assess OEF in clinical cohorts of cognitively impaired and healthy elderly subjects. Based on the hypothesis that cognitive impairment and dementia are predicted by age and white matter hyperintensities, this study investigated the effect of these two factors on OEF.…”
Section: Applications To Aging and Neurodegenerationmentioning
confidence: 99%